Feedback in English Writing for Indonesian EFL Students - Herlinawati Herlinawati (ELT-Lectura, 2014)
This study provides an overview about the feedback given to the students’ English writing. The essential of feedback in teaching writing for Indonesian EFL students due to the shift from process to product is becoming the rationale of this study. Student writing is often influenced by the students’ writing concept in addressing their ideas in Indonesian writing and English context as Foreign Language (EFL) in which is different. As giving feedback is one of the teachers’ tasks, the study on teachers’ perception on students’ writing and students’ perceptions on teachers’ responses need to be done. Some previous researchs on writing have been conducted on English department students in Lancang Kuning University. This study intends to get the views how feedback is given in EFL classroom in which the findings of the study is expected to know the needs of the students on their EFL writing in accomplishing good writing.